2013
DOI: 10.5114/ninp.2013.39075
|View full text |Cite
|
Sign up to set email alerts
|

Czy wskaźnik masy ciała i stężenie lipidów w surowicy wpływają na częstość występowania i przebieg migreny?

Abstract: Migraine is a well-known condition for many medical specializations. Some authors evaluate the potential impact of the abnormal body mass index (BMI) and abnormal lipid profile on the vulnerability to migraine and its severity. Regarding the fact that these factors have the inseparable connection with the risk of cardiovascular diseases, some papers bring the hypotheses of the probable role of migraine in the progression of such conditions. Some research suggests a link between abnormal BMI and a risk of migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“… 29 Chorazka et al observed that the levels of TC and low-density lipoprotein cholesterol may contribute to an increased risk of migraine in Polish subjects. 34 In this study, we observed no differences in lipid concentrations between the patients with migraine and control individuals. These conflicting findings may be related to the different dietary habits of the Chinese population.…”
Section: Discussioncontrasting
confidence: 45%
“… 29 Chorazka et al observed that the levels of TC and low-density lipoprotein cholesterol may contribute to an increased risk of migraine in Polish subjects. 34 In this study, we observed no differences in lipid concentrations between the patients with migraine and control individuals. These conflicting findings may be related to the different dietary habits of the Chinese population.…”
Section: Discussioncontrasting
confidence: 45%